Steering Future Research in Microfinance : Standing Atop Existing Literature - Vijaykumar, N. V. (Arthshastra Indian Journal of Economics & Research, 2022)
Microfinance has attracted a wide array of researchers worldwide, and as a result, there has been a humungous amount of literature on the subject. Research on microfinance has far-reaching practical implications as it impacts global poverty, thereby providing valuable insights to governments, economists, and non-governmental organizations. However, research on microfinance is constrained by several aspects, as observed by many researchers on the subject. This paper reviewed the existing literature on microfinance and elaborated on the factors that obfuscate the path to a clear understanding of the subject. One such example is the equivocal stance taken by researchers on whether microfinance is restricted to microcredit only or whether it includes other social interventions like training and forming groups. Another factor that undermines research on the subject is the unavailability of granular data, which hinders research on microfinance’s social and financial intermediation aspects. These deterrents to more hygienic research on microfinance have been highlighted in this paper. This review helped steer future research into less charted areas like the cost of social intermediation, separating the effects of social and financial intermediation, and avoiding confusion in the constituents of microfinance. Future researchers must avoid these pitfalls so that their work leads to more meaningful conclusions and is free from anomalies hitherto flagged.